Pigments measured on MUC samples during Island Pride cruise IP21 (MANGAN21) to the GSR license area in the Clarion Clipperton Fracture Zone - Lara Macheriotou; Bruno Vlaeminck; Bart Beuselinck; Nene Lefaible; Jolien Goossens; Ann Vanreusel (PANGAEA, 2022)
This dataset contains sedimentary parameters pigments (Chlorophyll a, Pheophorbide, Pheophytin) measured from Multicorer (MUC) samples from the Global Sea Mineral Resources (GSR, Belgium) license area in the Clarion Clipperton Fracture Zone (CCFZ) collected on onboard the Norwegian Island Pride during expeditions Mangan21 in 2021. Pigment analysis was completed according to Van Heukelem and Thomas (2001). After addition of 90% acetone, freeze-dried samples were sonicated and extracted overnight at 4°C. After filtration, the extract was injected into an Agilent HPLC with fluorescence detector (type 1200 Infinity II, Agilent Technologies, Diegem, Belgium) equipped with an Eclipse XDB C8 column. The sum of Chl-a and phaeopigment concentrations was calculated and is referred to as the Chloroplast Pigment Equivalent (CPE). These data were collected to quantify primary productivity in the CCFZ and to correlate these values to observed levels of biodiversity. Values are given in their respective units (SI) and have been collected and measured by the Marine Biology Research Group of Ghent University (Belgium).